2020
DOI: 10.1007/s42729-020-00354-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Understanding Fluoride Accumulation, Toxicity, and Tolerance Mechanisms in Plants: an Overview

Abstract: Excess fluoride (F − ) inhibits the growth and metabolism of several crop plants, while some have an innate ability for F − tolerance. The present study was undertaken to explain how plants tolerate F − toxicity and understand the efficacy of exogenous stress protectants and phytoremediation approaches for F − homeostasis and tolerance of crop plants. This review comprehends existing information available so far on the F − accumulation toxicity and tolerance mechanisms. A high level of F − inhibits plant growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 102 publications
(167 reference statements)
0
10
0
2
Order By: Relevance
“…Fluoride (F − ) is a well-known pollutant in the environment for its highly reactive and non-biodegradable nature, which ranks 13 th in abundance in the Earth’s crust [ 21 , 22 ]. Most of the research findings in plants suggest that excessive accumulation of fluoride causes phytotoxicity [ 21 ]. However, fluoride at low concentrations is beneficial in the prevention of dental caries and facilitates the mineralization of hard tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride (F − ) is a well-known pollutant in the environment for its highly reactive and non-biodegradable nature, which ranks 13 th in abundance in the Earth’s crust [ 21 , 22 ]. Most of the research findings in plants suggest that excessive accumulation of fluoride causes phytotoxicity [ 21 ]. However, fluoride at low concentrations is beneficial in the prevention of dental caries and facilitates the mineralization of hard tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride is a common phytotoxic contaminant for plants [190]. Plant species absorb fluoride from water and soil via roots and air through leaves [190,191], accumulate fluoride in different parts of the plant, and acquire fluoride at a higher level than in the environment [192,193]. Fluoride accumulation in plants depends on various factors such as fluoride concentration in soil, plant species, and soil properties [178].…”
Section: Fluoride Uptake and Bioaccumulation In Plants And Foodsmentioning
confidence: 99%
“…The minimal optimal limit for fluoride accumulation in plants is 10 mg L −1 ; however, fluoride uptake levels in Trifolium repens and Lolium multiflorium were 30 mg kg −1 and 50 mg kg −1 [197]. Therefore, it has been reported that fluoride toxicity can adversely impact seed germination, cellular enzymatic activity, crop yield, etc., as shown in Table 1 [191,[198][199][200][201][202]. Shoot tip burning and chlorosis, reduction in abscisic acid, and inhibition of polyamine biosynthesis and the ascorbate-glutathione cycle [206] Rice (Oryza sativa)…”
Section: Fluoride Uptake and Bioaccumulation In Plants And Foodsmentioning
confidence: 99%
See 2 more Smart Citations